Analysis of different training models for handball goalkeepers - Alejandro Muñoz Moreno; Ernesto Martín Redondo; Jorge Lorenzo Calvo; Jesús Rivilla-García (Federación Extremeña de Balonmano; University of Extremadura, 2012)
The importance of the goalkeeper for the team performance is critical, however, publications on specific preparation are few in number, with no clear lines of work. The present study aims to analyze the different methodologies used in the specific training handball goalkeeper, by setting what the different training models as well as deepen the potential applications of each. For this purpose, it was conducted an extensive literature review, categorizing each document based on the performance factor on which prioritizes: physical-technical, perceptual and tactical. The analysis of results found that there were no other models than those categorized, being more numerous publications falling under physical and technical training, followed by the perceptive and very few exist on tactical training. In light of the results seems essential to conduct a specific training program for goalkeeper, taking into account the most relevant variables for optimal performance. No single factor seems more relevant to any stage of training, it being necessary to deepen it. Keywords: specific training, perception, decision making, tactical